2016
DOI: 10.1371/journal.pone.0150114
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TREM-1 and Dectin-1 Alleviates the Severity of Fungal Keratitis by Modulating Innate Immune Responses

Abstract: PurposeTo explore the possibility that inhibiting triggering receptor expressed on myeloid cells-1 (TREM-1) and Dendritic cell-associated C-type lectin-1(Dectin-1) could modulate the innate immune response and alleviate the severity of corneal fungal keratitis.MethodTREM-1 and Dectin-1 expression was detected in fungus-infected human corneal specimens by real-time PCR. C57BL/6 (B6) mice were injected with Aspergillus fumigatus and divided into 4 groups that received subconjunctival injections of PBS and IgG as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…TREM-1 activation can amplify TLRs and NLRs signaling to promote the production of pro-inflammatory cytokines, degranulation of neutrophils, and phagocytosis 111213. Depletion or blocking TREM-1 has shown protective effects in sepsis, ischemia-reperfusion, pancreatitis, inflammatory bowel diseases, Fungal Keratitis and arthritis14151617181920. Our previous study found that the expression of TREM-1 in LPS-induced ALI mice lung and macrophages are significantly increased, suggesting an important role of TREM-1 in ALI2122.…”
mentioning
confidence: 99%
“…TREM-1 activation can amplify TLRs and NLRs signaling to promote the production of pro-inflammatory cytokines, degranulation of neutrophils, and phagocytosis 111213. Depletion or blocking TREM-1 has shown protective effects in sepsis, ischemia-reperfusion, pancreatitis, inflammatory bowel diseases, Fungal Keratitis and arthritis14151617181920. Our previous study found that the expression of TREM-1 in LPS-induced ALI mice lung and macrophages are significantly increased, suggesting an important role of TREM-1 in ALI2122.…”
mentioning
confidence: 99%
“…Following the infection of T. gondii , innate cells, including macrophages, dendritic cells, and neutrophils, are recruited to the sites of infection, producing proinflammatory cytokines, phagocytizing the parasites, or generating reactive chemical substances in order to inhibit the replication and dissemination of the parasites ( 46 49 ). Human NPY, LGALS1, S100A12, SAA1, and TREM1 have been reported as regulators of innate immunity, modulating the innate immune functions by controlling the innate cells physiology and cytokines release ( 50 55 ). In this study, NPY, LGALS1, and TREM1 were found as targets of ROP18 I , and S100A12, SAA1, and TREM1 were targets of ROP18 II .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the presence of high number of neutrophils may be a major source of IL-12 detected in the lung from infected-Lgals1 −/− mice, as neutrophils have been reported to produce IL-12 [ 54 ]. Curiously, inhibition of dectin-1 expression, a host receptor for fungal beta-glucan, reduces the severity of fungus infection and its effect was associated with decrease of proinflammatory cytokines, including IL-12, and neutrophil infiltration [ 55 ]. Furthermore, it is known that proinflammatory cytokines, including IL-12 [ 32 , 34 , 56 , 57 ], are essential for host defense against H. capsulatum .…”
Section: Discussionmentioning
confidence: 99%